2011
DOI: 10.1038/ajg.2011.360
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Stenting as a Bridge to Surgery in Malignant Large-Bowel Obstruction: A Report from Two Large Multinational Registries

Abstract: OBJECTIVES:To date, this is the largest prospective series in patients with malignant colorectal obstruction to evaluate the effectiveness and safety of colonic self-expanding metal stents (SEMSs) as an alternative to emergency surgery. SEMSs allow restoration of bowel transit and careful tumor staging in preparation for elective surgery, hence avoiding the high morbidity and mortality associated with emergency surgery and stoma creation. METHODS:This report is on the SEMS bridge-to-surgery subset enrolled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(50 citation statements)
references
References 34 publications
(44 reference statements)
3
42
0
3
Order By: Relevance
“…In a paper by Vitale et al, up to 10 % of the patients in their review had a synchronous cancer, and as a result of being able to have preoperative stenting, they were able to have a full evaluation and make a more educated surgical resection plan. [28][29][30][31][32][33] In addition, a costeffectiveness analysis concluded that colonic stent insertion followed by surgery was more effective and less costly than emergency surgery, especially when looking at the patient's quality of life. 25 A multi center study showed that colonic stenting relieved the obstruction in 93 % of patients, and as a result, 92 % of patients were able to undergo a single-stage resection and anastomosis within 8.6 days of stent placement, with only one patient having a perforation.…”
Section: Bridge To Surgerymentioning
confidence: 99%
“…In a paper by Vitale et al, up to 10 % of the patients in their review had a synchronous cancer, and as a result of being able to have preoperative stenting, they were able to have a full evaluation and make a more educated surgical resection plan. [28][29][30][31][32][33] In addition, a costeffectiveness analysis concluded that colonic stent insertion followed by surgery was more effective and less costly than emergency surgery, especially when looking at the patient's quality of life. 25 A multi center study showed that colonic stenting relieved the obstruction in 93 % of patients, and as a result, 92 % of patients were able to undergo a single-stage resection and anastomosis within 8.6 days of stent placement, with only one patient having a perforation.…”
Section: Bridge To Surgerymentioning
confidence: 99%
“…In this setting, colonic stents represent the best option when skills are available [7] . [18] 2008 51 51 (100) 43 (84.3) 1 (1.9) Fernández-Esparrach et al [19] 2010 47 44 (94) 44 (94) 3 (7) Small et al [20] 2010 233 224 (96.1) 222 (95.2) 18 (7.7) Park et al [21] 2010 151 149 (98.6) 140 (92.7) 0 Branger et al [22] 2010 93 86 (92.5) 80 (86) 3 (3.2) Donnellan et al [23] 2010 43 40 (93) 40 (93) 2 (4.6) Lee JH et al [24] 2010 46 46 (100) 39 (84.8) 2 (4.3) Lee HJ et al [25] 2011 71 68 (95.8) 68 (94) 4 (5.6) Luigiano et al [26] 2011 39 36 (92.3) 35 (89.7) 2 (5.1) Jiménez-Pérez et al [27] 2011 182 177 (98) 141 (94) 5 (3) Tominaga et al [28] 2012 24 24 (100) 20 (83) 0 Yoshida et al [29] 2013 33 33 (100) 32 (97) 0 Bonfante et al [30] …”
Section: Resultsmentioning
confidence: 99%
“…In recent years, with the rise in the mortality and morbidity rates of CRC, malignant colonic obstruction has been causing more complicated clinical problems in CRC patients (Jimenez-Perez et al, 2011;Song and Baron, 2011;van Hooft et al, 2011). Surgical colectomy is still considered the best and final choice for the treatment of LMCO (Song and Baron, 2011;van Hooft et al, 2011).…”
Section: Discussionmentioning
confidence: 99%